Defense Diplomacy in Peace Time to Strengthening Military Partnership and Enhancing Defense Capabilities between Indonesia and France through the Acquisition of Rafale Jets - Styawati, Ika Hijria; Almubaroq, Hikmat Zakky; Rishdianto, Agung; Duarte, Editha P (CV. AFDIFAL MAJU BERKAH, 2023)
Defence diplomacy, also referred to as military diplomacy, involves the peaceful utilization of armed forces to enhance a nation's diplomatic relations and advance its global objectives. This is achieved through various means such as officer exchanges, joint training initiatives, cultural interactions, and reciprocal naval visits, among others. This abstract explores the significance of defense diplomacy during times of peace in strengthening military partnerships and enhancing defense capabilities between Indonesia and France, with a specific focus on the acquisition of Rafale jets. Defense diplomacy serves as a crucial tool for fostering international relations and promoting regional stability. The procurement of advanced military aircraft such as the Rafale jets not only bolsters Indonesia's defense capabilities but also deepens the bilateral defense cooperation between the two nations. This research will use qualitative research methods. This research was conducted using a qualitative descriptive research approach utilizing the literature review method. The literature review was performed by the researcher by utilizing various secondary data sources such as books, journal articles, press releases, news articles, as well as institutional websites. The abstract highlights the benefits of the Rafale jets in terms of their advanced technology, versatility, and interoperability, enabling Indonesia to address various security challenges effectively. Moreover, it emphasizes the positive impact of this strategic acquisition on defense industry collaboration, technology transfer, and human capital development. By strengthening military partnerships and enhancing defense capabilities through the acquisition of Rafale jets, Indonesia and France can pave the way for mutually beneficial and sustainable defense cooperation, contributing to regional security and stability.